Typification of Adelia resinosa, the basionym of Mallotus resinosus (Euphorbiaceae), and its three new synonyms from India - Chakrabarty, Tapas; Krishna, Gopal (Phytotaxa, 2020)
The species Mallotus aureopunctatus, M. beddomei and M. lawii are merged under the variable and widespread M. resinosus. A second-step neotype is designated for the name Adelia resinosa while lectotypes are designated for M. beddomei and Rottlera aureopunctata.